Exploring audience response system: impacts in learning institutions - Mamangkiang Mantikayan, J.; Ayu, Media Anugerah (2010)
Audience response system is a form of interactive learning that aims to enhance the learning experience by connecting each student to the teacher. In a traditional lecture format class, students use personalized and varying techniques to best absorb the material. It is interesting to explore the impact of audience response system in learning institution. This paper explores audience response system (ARS), benefits, disadvantages and challenges in learning institution environment. The findings shows that majority of the literature encourage the use of audience response system in learning institutions.